2018
DOI: 10.1155/2018/5190693
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Approach Based on Wearable Inertial Sensors to Assess and Identify Motion and Errors in Techniques Used during Training of Transfers of Simulated c-Spine-Injured Patients

Abstract: Patients with suspected spinal cord injuries undergo numerous transfers throughout treatment and care. Effective c-spine stabilization is crucial to minimize the impacts of the suspected injury. Healthcare professionals are trained to perform those transfers using simulation; however, the feedback on the manoeuvre is subjective. This paper proposes a quantitative approach to measure the efficacy of the c-spine stabilization and provide objective feedback during training. Methods. 3D wearable motion sensors are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This phenomenon was observed for a non-traumatic flexion moment (2 Nm) which shows the importance of post-traumatic immobilization in comparison. Since this happened at 51 degrees of C2-T1 flexion, it shows that the mobility permitted by cervical collars is not sufficiently restrictive: 40.8 degrees of maximal head flexion measured on voluntary subjects (Lebel et al 2018) and 30 degrees of neck flexion measured on cadavers with a cervical instability (Horodyski et al 2011).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This phenomenon was observed for a non-traumatic flexion moment (2 Nm) which shows the importance of post-traumatic immobilization in comparison. Since this happened at 51 degrees of C2-T1 flexion, it shows that the mobility permitted by cervical collars is not sufficiently restrictive: 40.8 degrees of maximal head flexion measured on voluntary subjects (Lebel et al 2018) and 30 degrees of neck flexion measured on cadavers with a cervical instability (Horodyski et al 2011).…”
Section: Discussionmentioning
confidence: 93%
“…A study conducted on healthy volunteers showed that different CC were mostly successful at reducing axial rotation while 19.8 to 40.7 % of flexion is preserved compared to no collar (Kim et al 2018). Log-roll transfers simulations performed by paramedics on healthy volunteers wearing a CC showed peak relative head motion of 9.5 to 40.8 degrees (Lebel et al 2018). Horodyski et al (2011) measured around 30 degrees of flexion on a cadaver model wearing a CC with a C5-C6 global instability.…”
Section: Introductionmentioning
confidence: 99%
“…In regards to wearable sensors, Lebel et al found that the use of motion sensors affixed to standardized patients allowed researchers to provide more specific, quality feedback to learners enabling them to more easily correct emergency rolling techniques performed on c-spine injured patients. Researchers found that the use of wearable inertial sensors provided instructors with objective data to provide personalized feedback during training and could be further employed to provide a complete training solution by directly embedding the inertial sensors into mannequins ( *Lebel, Chenel, Boulay, & Boissy, 2018).…”
Section: Health Care Disciplines Represented In Past Researchmentioning
confidence: 99%
“…The high-fidelity mannequin used to collect CSM during alpine rescue simulations was developed by our group based on previous c-spine management best practice research [ 37 39 ]. The mannequin measures 175 cm and weighs 82 proportionally distributed kilograms.…”
Section: Methodsmentioning
confidence: 99%